Respuesta :

Answer:

[tex]y = \frac{1}{6}x - 4[/tex]

[tex]y = \frac{x}{2} + 2[/tex]

[tex]y = \frac{1}{8}x[/tex]

[tex]y = \frac{1}{6}x+ \frac{2}{3}[/tex]

[tex]y = 12x - 9[/tex]

Step-by-step explanation:

Required

Represent in gradient intercept form

This means that the equation be in form: [tex]y = mx + c[/tex]

Solving (a): [tex]3y = \frac{1}{2}x - 12[/tex]

Divide through by 3

[tex]\frac{3y}{3} = \frac{1}{3*2}x - \frac{12}{3}[/tex]

[tex]y = \frac{1}{6}x - 4[/tex]

Solving (b): [tex]5x = 10y - 20[/tex]

Make y the subject

[tex]10y = 5x + 20[/tex]

Divide through by 10

[tex]y = \frac{5x}{10} + \frac{20}{10}[/tex]

[tex]y = \frac{x}{2} + 2[/tex]

Solving (c): [tex]x = 8y[/tex]

Make y the subject

[tex]8y= x[/tex]

Divide through by 8

[tex]y = \frac{1}{8}x[/tex]

Solving (d): [tex]\frac{1}{2}x = 3y - 2[/tex]

Make y the subject

[tex]3y = \frac{1}{2}x+ 2[/tex]

Divide through by 3

[tex]y = \frac{1}{2*3}x+ \frac{2}{3}[/tex]

[tex]y = \frac{1}{6}x+ \frac{2}{3}[/tex]

Solving (d): [tex]\frac{2}{3}y - 8x = -6[/tex]

Make y the subject

[tex]\frac{2}{3}y = 8x -6[/tex]

Divide through by 3/2

[tex]\frac{3}{2} * \frac{2}{3}y =\frac{3}{2} * ( 8x -6)[/tex]

[tex]y =\frac{3}{2} * ( 8x -6)[/tex]

[tex]y =\frac{3}{2} * 8x -\frac{3}{2} * 6[/tex]

[tex]y = 3 * 4x - 3 * 3[/tex]

[tex]y = 12x - 9[/tex]